The PENGARUH RELIGIUSITAS, HALAL KNOWLEDGE, HALAL AWARENESS, DAN SIKAP KONSUMEN TERHADAP NIAT BELI PRODUK SKINCARE HALAL BLP SKIN - Salsabilla Aura Balqis; Siti Zulaikha (Jurnal Bisnis dan Manajemen (JBM), 2023)
The purpose of this study is to determine the effect of religiosity, halal knowledge, halal awareness and attitude on consumer’s purchase intention towards skincare product BLP Skin in Kota Surabaya. The data was collected from online questionnaires. This study used a quantitative method and was tested using SEM PLS by SmartPLS. The result of this study found that religiosity significantly influenced attitude and consumer intention to buy skincare BLP Skin. Halal knowledge also significantly influenced consumer’s attitude, and lastly halal awareness had significant influence towards consumer’s purchase intention. Meanwhile, the relationship between halal knowledge and purchase intention, halal awareness towards attitude, also attitude and purchase intention were found to be not significant. Finally, for the mediating effect in this study found that there were no mediation with purchase intention through attitude. The results give implication to firms competing in cosmetic industry. Halal awareness is one of the main factor that should be taken into account in promoting their product.